Reminded by the instruments: David Tudor's music - Nakai, Yu (New York Oxford University Press, 2021)
"David Tudor (1926-1996) is remembered today in two guises: as an extraordinary pianist of postwar avant-garde music who worked closely with composers like John Cage and Karlheinz Stockhausen, influencing the development of graphic notation and indeterminacy; and as a spirited pioneer of live-electronic music who realized idiosyncratic performances based on the interaction of homemade modular instruments, inspiring an entire generation of musicians. However, the fact that Tudor himself did not talk or write much about what he was doing, combined with the esoteric nature of electronic circuits and schematics (for musicologists), has prevented any comprehensive approach to the entirety of his output which actually began with the organ and ended in visual art. As a result, Tudor has remained a puzzle of sorts in spite of his profound influence-perhaps a pertinent status for a figure who was known for his deep love of puzzles. This book sets out to solve the puzzle of David Tudor as a puzzle that David Tudor made, applying Tudor's own methods for approaching other people's materials to the unusually large number of materials that he himself left behind. Patching together instruments, circuits, sketches, notes, diagrams, recordings, receipts, letters, custom declaration forms, testimonies, and recollections like modular pieces of a giant puzzle, the narrative skips over the misleading binary of performer/composer to present a lively portrait of Tudor as a multi-instrumentalist who always realized his music from the nature of specific instruments"--
Keywords: Composing; Piano; Avant-garde